KETIDAKADILAN GENDER TERHADAP PEREMPUAN DALAM NOVEL KARTINI KARYA ABIDAH EL KHALIEQY - Oktavianingsih, Wulan; Martono, Martono; Wartiningsih, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe purpose of this research was to describe the types of gender injustice in the form of violence, types of gender injustice in the form of marginalization, types of gender injustice in the form of subordination, types of gender injustice in the form of stereotypes and implementation plans of research results of gender injustice forms in Abidah El Khalieqy's novel, Kartini, on college's learning literature. This research was theoretically and practically useful. The theories used in this study were feminism, gender, gender injustice, women, literary criticism of feminism, novels, and literature study. This research uses descriptive method, in the form of qualitative, with a literary criticism of feminism approach. The data source was Kartini's novel by Abidah El Khalieqy with data in the form of excerpts that show the types of gender injusticeexperienced by female figures illustrated in the sentences in the novel of Kartini by Abidah El Khalieqy. Data collection techniques using indirect techniques, in the form of documentary techniques and data collection tools were researchers themselves as the main instrument. The technique of testing the validity of the data using perseverance observation, triangulation, and sufficiency of references.Keywords: Kartini, Novel, Study of Feminism